PENGEMBANGAN MODUL BERBASIS GUIDED NOTE TAKING (GNT) PADA PEMBELAJARAN KIMIA SMA - Suriani, Teti; Utami, Lisa (Journal of Chemistry Education and Integration, 2022)
Abstract This research aimed at designing Guided Note Taking (GNT) based module that was valid based on the validation by the experts of material and media, teacher practicality, and student response on Atomic Structure and Periodic System of the Elements lesson. It was R&D (Research and Development) with 4-D development model. It was administered at State Senior High School 12 Pekanbaru and it was conducted to the tenth-grade students of MIPA 4. The module could be stated proper if it complied the valid and practical aspects. Validity could be seen from the results of validation that the validation sheet was used. The percentage of the validation result by the experts of material overall was 94.74% and it was on very valid category. The percentage of the validation result by the experts of media overall was 86.6% and it was on very valid category. Practicality test was conducted to 3 teachers and it was obtained the result 84.44% and it was on very practical category. Student responses were obtained from 20 students, and the questionnaire result was 81.06% and it was on very good category. Keywords : Module, Guided Note Taking, Atomic Structure and Periodic System of the Elements